Magnetic structures of Laves phase superlattices - Bentall, M; Cowley, R; Buyers, W; Tun, Z; Lohstroh, W; Ward, R; Wells, MR (2003)
The magnetic structure of Laves phase superlattices of structure [70/30]60, [150/100]50 and [50/70]60 were discussed. It was found that the [50/70]60 sample showed unexpected behavior because the moments aligned largely perpendicular to an applied field. The net moments on the DyFe2 and YFe2 layers were also discussed.